(untitled) (Universal International Scientific Journal, 2026)
This article scientifically analyzes the problem of addiction to online gambling and its connection with the individual psychological characteristics of the individual. In the course of the research, the influence of such factors as personality traits, impulsivity, stress resistance, motivational factors, and socio-psychological adaptation on the tendency to online gambling was studied. The psychological mechanisms of this problem and ways to prevent it were also highlighted based on scientific sources.